Bridging techno-divide in Tahfiz education with digital skill training / Intan Syaherra Ramli, Muhammad Hafiz Saleh and Anitawati Mohd Lokman - Ramli, Intan Syaherra; Saleh, Muhammad Hafiz; Mohd Lokman, Anitawati (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Ministry of Education Malaysia indicates that there are 1,198 registered Tahfiz schools with JAKIM and 1135 of these are private schools that run the schools based own their resources. This means that the field of Tahfiz is expanding and has the potential to produce professional Huffaz in the science and technology field. In conjunction with this, Persatuan Permata Al-Quran Malaysia (PERMATA) is an NGO association in Malaysia that also plays a role in the development and enhancement of Tahfiz education. This is to ensure it meets with the modern education system and at the same time retains its traditional values in Tahfiz education. Previous research show that, there is a significant need to tackle the issue of digital literacy within Tahfiz education institutions. The issue related to limited technology access, and less digital skills such as documentation in word processing, excel and graphic design for presentation skills among Tahfiz students and teachers [1][2][3][4]. It also aligns with the Research on Policies, Management, and Curriculum of Tahfiz Students in Malaysia in 2022 which mentions about the initiative to improve the digital competencies that can be applied in the Tahfiz education curriculum. It also contributes to the Sustainable Development Goal (SDG) to improve the quality of education and reduce inequalities. In addition, the initiative also benefits the communities with low income (B40) by enhancing the educational quality and technology usage in long life learning. Thus, there is a need to offer the necessary training in digital software to meet this challenge.